Masi methodology: centring Pacific women's voices in research. (September 2019) - Naepi, Sereana
Masi methodology is a Pacific women centred research methodology. Using masi as an anchoring metaphor for research ensures that research centres Pacific women's voices, understands that Pacific women's voices are valuable and provides a way to acknowledge that the knowledge Pacific women hold is useful for generations to come. Building on previously articulated Pan-Pacific research methodologies and methods, masi as methodology specifies that the Pacific women be centred within the research process. Masi methodology like other Pacific research methodologies and methods is capable of being both Pan-Pacific and regionally specific dependent on which community the research is being conducted with. In its current form, masi methodology is not a method; however, like other Pacific research methodologies and methods, it is expected that masi methodology will grow as more Pacific researchers use and engage with the masi methodology.